Vincent van Gogh and the Birth of Cloisonism - Welsh-Ovcharov, Bogomila (Toronto : Art Gallery of Ontario, 1981)
Gauguin, Paul ; Anquetin, Louis ; Bernard, Emile ; de Toulouse-Lautrec, Henri ; Meyer de Haan, Jakob ; Laval, Charles ; Sérusier, Paul ; Denis, Maurice
Vincent van Gogh and the Birth of Cloisonism, Art Gallery of Ontario, Toronto, 24 january - 22 march 1981, Rijksmuseum Vincent Van Gogh, Amsterdam, 9 april - 14 june 1981
boek
Keywords: Van Gogh, Vincent